Pembangunan Air Bersih dan Sanitasi saat Pandemi Covid-19 - Suryani, Anih Sri (Jurnal Aspirasi, 2020)
Sanitation development in Indonesia refers to the Sustainable Development Goals, which in 2030 is targeted to ensure the availability and management of clean water and sustainable sanitation for all. The existence of the Covid-19 pandemic has made the clean water and sanitation sector very important in breaking the Covid-19 chain. This paper aims to describe the achievement of sanitation development targets in Indonesia and examine the empirical practice of implementing sanitation during the Covid-19 pandemic. Qualitative methods are used to assess the sanitation sector according to the sixth SDGs Target, namely: clean water and proper sanitation both before the pandemic and during the pandemic. The results of the study show that until 2019, before the pandemic, access to drinking water, wastewater, and sanitation services had been achieved quite well. However, the reduction in open defecation (BABS) and the improvement of clean and healthy living behavior (PHBS) have not been optimal. When the Covid-19 pandemic consumption of clean water increases, attention to wastewater treatment increases, and there are changes in people's behavior to live cleaner lives.AbstrakPembangunan sanitasi di Indonesia mengacu pada Sustainable Development Goals di mana pada tahun 2030 ditargetkan dapat menjamin ketersediaan serta pengelolaan air bersih dan sanitasi yang berkelanjutan untuk semua. Adanya pandemi Covid-19  menjadikan sektor  air  bersih dan sanitasi sangatlah penting dalam memutus mata rantai Covid-19. Tulisan ini bertujuan untuk menggambarkan capaian target pembangunan sanitasi di Indonesia dan mengkaji praktik empiris penyelenggaraan sanitasi pada saat pandemi Covid-19. Metoda kualitatif digunakan untuk mengkaji sektor sanitasi sesuai dengan Target SDGs keenam, yaitu: air bersih dan sanitasi layak, baik sebelum pandemi maupun saat pandemi. Hasil kajian menunjukkan bahwa hingga 2019, sebelum pandemi akses terhadap air minum, air limbah dan layanan sanitasi telah tercapai dengan cukup baik. Namun penurunan praktik Buang Air Besar Sembarangan (BABS) dan peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) belum optimal. Saat pandemi Covid-19 konsumsi air bersih meningkat, perhatian pada pengolahan air limbah meningkat, dan ada perubahan perilaku masyarakat untuk hidup lebih bersih.